Exploring forms of life in player development pathways - the case of British rugby league - Rothwell, M.; Davids, K.; Stone, J. (Journal of Motor Learning and Development, 2018)
This study highlighted how interacting subsystems in player development pathways collide to create many forms of life in sport, which results in conflicting beliefs and attitudes towards coaching and player development.